The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.3151/jact.9.231
|View full text |Cite
|
Sign up to set email alerts
|

Semi-quantitative Prediction of the Corrosion Risk of Steel in Concrete Using XRD Analysis

Abstract: The present study concerns a technique for determining the chloride binding capacity, using the XRD curve containing the peaks for Friedel's salt. The influence of chloride binding on the corrosion behaviour was also evaluated. The binding capacity of chloride ions in cement paste was determined by the water extraction method. As a result, it was found that the chloride binding capacity is strongly dependent on the W/C, binder type, curing age and total chloride concentration in the paste. It is notable that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The role of chloride binding at steel corrosion in concrete is subjected to debate. For example, Kim et al [15] suggested that there was no clear-cut relation between chloride binding and corrosion risk on the stage of corrosion initiation, although the rate of corrosion propagation might be affected by concentration of free chlorides, in turn binding capacity of chlorides. Glass et al [16] support this hypothesis that no influence of chloride binding on the corrosion risk is given, as the bound chloride chlorides could be released to be free in the vicinity of steel due to a pH fall from the electrochemistry on the steel surface.…”
Section: Resultsmentioning
confidence: 99%
“…The role of chloride binding at steel corrosion in concrete is subjected to debate. For example, Kim et al [15] suggested that there was no clear-cut relation between chloride binding and corrosion risk on the stage of corrosion initiation, although the rate of corrosion propagation might be affected by concentration of free chlorides, in turn binding capacity of chlorides. Glass et al [16] support this hypothesis that no influence of chloride binding on the corrosion risk is given, as the bound chloride chlorides could be released to be free in the vicinity of steel due to a pH fall from the electrochemistry on the steel surface.…”
Section: Resultsmentioning
confidence: 99%